The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1179/1351000215y.0000000012
|View full text |Cite
|
Sign up to set email alerts
|

Serum paraoxonase and arylesterase activities in patients with chronic otitis media

Abstract: These results indicated that a lower level of PON1 activity was associated with an oxidant-antioxidant imbalance. In addition, decreased PON1 activity may play an important role in the pathophysiology of COM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The second study identified was by Turan et al [24] The level of lipid hydroperoxide (LOOH) was investigated in this study in addition to the same parameters used by Baysal et al [12] in their study. Turan et al [24] discovered that serum PON and arylesterase activity was significantly lower, and the LOOH level higher, in patients with COM compared to individuals in their control group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The second study identified was by Turan et al [24] The level of lipid hydroperoxide (LOOH) was investigated in this study in addition to the same parameters used by Baysal et al [12] in their study. Turan et al [24] discovered that serum PON and arylesterase activity was significantly lower, and the LOOH level higher, in patients with COM compared to individuals in their control group.…”
Section: Discussionmentioning
confidence: 99%
“…The second study identified was by Turan et al [24] The level of lipid hydroperoxide (LOOH) was investigated in this study in addition to the same parameters used by Baysal et al [12] in their study. Turan et al [24] discovered that serum PON and arylesterase activity was significantly lower, and the LOOH level higher, in patients with COM compared to individuals in their control group. They state that low serum PON1 activity may be considered an indicator of oxidant-antioxidant imbalance, claiming in addition that low serum PON1 activity may have an important role to play in the pathogenesis of COM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Free radicals can attack cell membranes, proteins, and DNA, causing irreparable damage and ultimately cell death. 15,19 ROS, including superoxide radicals and hydroxyl radicals, can deplete cochlear tissues of antioxidant protective molecules. This may allow lipid peroxidation that can increase calcium influx and apoptosis in cells of the cochlea.…”
Section: Discussionmentioning
confidence: 99%